Oral health-related quality of life among Belgrade adolescents - Gajić, Milica; Lalić, Maja; Kalevski, Katarina; Marjanović, Marjan (Vojnosanitetski pregled, 2018)
Background/Aim. Adolescents are vulnerable group in term of acquisition of oral health-related knowledge, habits and attitudes. That is why the aim of this study was to investigate the associations between dental status, dental anxiety and oral health-related behavior and oral health-related quality of life as captured by Oral Impacts on Daily Performances (OIDP) index. Methods. This cross-sectional survey included representative sample of 404 adolescents (15 years old), randomly recruited from high schools in Belgrade, Serbia. The adolescents were interviewed using Serbian versions of eight-item OIDP index, Hiroshima University Dental Behavior Inventory (HU-DBI) and modified Corah’s Dental Anxiety Scale (MDAS). Three previously trained and calibrated dentists examined the subjects in the classrooms to determine the oral health status of adolescents [the Decayed, missing, filled teeth (DMFT) index and visual signs of gingivitis]. Results. At least one oral impact was reported in 49.50% of adolescents. Most frequently, oral health problems affected eating (26.73%), tooth cleaning (27.47%) and sleep and relaxation (16.83%). In comparison with adolescents without oral impacts, the adolescents with at least one oral impact reported, had higher DMFT score, more often reported problems with bleeding gums, usage of hard toothbrush, worries about the color of their teeth and seeing the dentist because of the symptoms. Logistic regression showed that dental anxiety (MDAS score), dental behavior (HU-DBI score) and worrying about the color of the teeth significantly affected OIDP score. Conclusion. Oral health-related quality of life among adolescents was affected by their behavior and dental anxiety levels. Implementing public health policies that target adolescents with poor oral health or bad habits might be helpful in improving their oral health-related quality of life.